The FY2008-FY2010 Medium-Term Administrative and Capital Budgets. (Policy Papers; Policy Paper ;, 2007)
This paper presents proposals for the FY2008-FY2010 medium-term budget (MTB) and seeks Board approval for the proposed FY2008 annual net administrative budget. The paper also presents the FY2008-FY2010 medium-term capital plan and seeks approval for expenditures on new capital projects beginning in FY2008. The impact of the proposed administrative and capital budgets on the Fund's administrative expenses (as classified in the Fund's financial statements), and hence on the Fund's net income over the next three years, is identified.